The Role and Importance of Fine Art in the Education of School Students - Muhammadiyeva Zarina Bahodirovna; Muhammadiyeva Ogiloy Rajabalievna (International Journal on Integrated Education, 2022)
The article provides information on the role and importance of fine arts in the education of schoolchildren. If every teacher knew how to draw perfectly, he would be very effective in teaching.